An Autoethnography About Recovering Awareness Following Brain Injury: Is My Truth Valid?. (January 2018) - Shankar, Sneha
This autoethnography confronts the assumptions and treatment of patients who have had a traumatic brain injury (TBI). TBI may be followed by deficits that can impact a person's self-awareness, and I describe my experience with this symptom. In this personal poetic narrative, I provide a glimpse into how I experienced typical symptoms of brain injury and illustrate the complexity of recovery. I suggest patient voices are too often discredited, which goes against the medical framework of patient-centeredness. I provide a voice to the lived experience of brain injury and illuminate the dehumanizing nature of being a patient of this injury.